Peculiarities in the course of chronic cerebral ischaemia in senior age groups in the dynamics of medical rehabilitation under conditions of a specialized medical center - T. F. Popova; L. A. Klimova (Бюллетень сибирской медицины, 2009)
According to the data of the investigation it was established the connection between the intensity of neurological and cognitive disturbances, psychoemotional disturbances and changes of quality of life of the adult and elderly patients with chronicle cerebral ischemia. It was showed that using the rehabilitation therapy in the special referral medical center in the beginning stage of the disease bias for the better on quality of live of the patients.